Epidemiological and demographic drivers of lung cancer mortality from 1990 to 2019: results from the global burden of disease study 2019 - Fan, Yaguang; Jiang, Yong; Gong, Lei; Wang, Ying; Su, Zheng; Li, Xuebing; Wu, Heng; Pan, Hongli; Wang, Jing; Meng, Zhaowei; Zhou, Qinghua; Qiao, Youlin (Frontiers in Public Health, 2023)
Background: Understanding the effects of demographic drivers on lung cancer mortality trend are critical for lung cancer control. We examined the drivers of lung cancer mortality at the global, regional and national levels. Methods: Data on lung cancer deaths and mortality were extracted from global burden of disease (GBD) 2019. The estimated annual percentage changes (EAPC) in lung cancer age-standardized mortality rate (ASMR) and All-age mortality were calculated to measure the temporal trends in lung cancer from 1990 to 1999. Decomposition analysis was used to analyze the contributions of epidemiological and demographic drivers to lung cancer mortality. Results: Despite of a non-significant decline of ASMR (EAPC=-0.31, 95% confidence interval (CI): -1.1-0.49), the number of lung cancer deaths increased 91.8% (95% uncertainty interval (UI): 74.5%-109.0%) from 1990 to 2019. This increase was driven by the change in number of deaths attributed to population aging (59.6%), population growth (56.7%) and risks outside GBD (3.49%) compared to 1990. Conversely, the number of lung cancer deaths due to GBD risks decreased 19.8%, and this decrease was most derived from tobacco (-12.66%), occupational risks (-3.52%) and air pollution (-3.47%). Increased number of lung cancer deaths (1.83%) from high fasting plasma glucose was observed in most regions. The temporal trend of lung cancer ASMR and the patterns of demographic drivers varied by region and gender. Significant associations between the contributions of population growth, GBD risks and risks outside GBD(negative) and population aging(positive) and ASMR in 1990, socio-demographic index (SDI) and Human Development Index (HDI) in 2019 were observed. Conclusions: The aging and growth of population resulted in an increase in global lung cancer deaths from 1990 to 2019, despite a decrease in age-specific death rate of lung cancer death from GBD risks in most regions. A Tailored strategy is warranted to wrestle the increased burden of lung cancer due to the outpaced demographic drivers on the epidemiologic change globally and in most regions with the consideration of region- or gender-specific risk patterns.